“But They’re Grad Students, They Should Know This”: Preliminary Findings from a Writing Center’s Hybrid Approach to Supporting Postgraduates in Qatar - Newsome, Mary; Mollazehi, Mohammad; Zidani, Mounia; Sheik, Randa; Amiry , Jumana (Online Learning, 2023)
Postgraduate research plays an important role in the knowledge economy, yet attrition rates among postgraduates remain a global concern. Numerous studies have cited anxiety around academic writing as a primary cause for declining completion rates, particularly among L2 students. Further exacerbating the problem is the acceleration of academic life where students are often expected to publish multiple papers prior to graduation. Despite assumptions that L2 postgraduates matriculate with requisite English academic writing skills, countless studies suggest otherwise. Such students face significant challenges developing these skills and accessing relevant institutional support, which calls for innovative solutions. This mixed-method comparative study analyzes historical data to understand the impact of a writing center’s hybrid approach to supporting the development of English academic writing skills among L2 postgraduates. Findings reveal that postgraduate students require flexibility in accessing academic writing support and prefer online and distance options over traditional, in-person support. Additionally, findings indicate that program faculty are willing to collaborate with writing centers to support students’ academic writing through a hybrid approach. Study findings also suggest that participants from the hybrid approach are more likely to publish prior to graduation compared to those from the traditional approach. These findings offer important insight for higher education administrators, writing centers, faculty, and postgraduate students as the “onlining” of higher education accelerates in the post-COVID era.